Minat Belajar dan Resiliensi Akademik Siswa SMK: Sebuah Studi Korelasional - Bayu Romadon; Nur Isnaini; Septian Lukman Hakim Isnaini Putra; Ahmad Efendy (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Learning interest plays a role in enhancing students’ attention, curiosity, and engagement in the learning process, while academic resilience supports students’ ability to cope with academic pressures and difficulties. This study aims to analyze the relationship between learning interest and academic resilience among vocational high school students. The study employed a quantitative approach with a non-experimental correlational design. The sample consisted of 31 eleventh-grade students of SMK Jayanegara selected through a saturated sampling technique. Data were collected using a five-point Likert-scale questionnaire and analyzed through descriptive statistics, prerequisite tests, and Pearson Product Moment correlation analysis. The results showed that students’ learning interest was predominantly in the moderate category (64.52%), while academic resilience was categorized as moderate (51.61%) to high (48.39%). The correlation test obtained a value of r = 0.684 with p < 0.001, indicating a positive, strong, and significant relationship between learning interest and academic resilience. These findings indicate that increased learning interest is associated with stronger students’ abilities to face academic challenges.